Staphylococcal superantigens evoke temporary and reversible T cell anergy, but fail to block the development of a bacterium specific cellular immune response - Heran Zhang; Ian R. Monk; Jessica Braverman; Claerwen M. Jones; Andrew G. Brooks; Timothy P. Stinear; Linda M. Wakim (Nature Communications)
Abstract Superantigens (sAgs) are bacterial virulence factors that induce a state of immune hyperactivation by forming a bridge between certain subsets of T cell receptor (TCR) β chains on T lymphocytes, and class II major histocompatibility complex (MHC-II) molecules; this cross-linking leads to indiscriminate T cell activation, cytokine storm and toxic shock. Here we show that sAg exposure drives the preferential expansion of naive and central memory T cell subsets, but not effector or resident memory T cells, which instead, hyper release pro-inflammatory cytokines. A targeted therapeutic approach to minimise cytokine release by effector memory T cells attenuated sAg-induced cytokine release. Irrespective of antigen experience, sAg activation does not render mature T cells permanently dysfunctional, and full restoration of effector function is observed following a transient and reversible anergy. Moreover, we show that in the face of sAg induced immune hyperactivation, an intact bacterium-specific CD4+ T cell response can be mounted.